Socioeconomic inequalities in immunisation of 12–23 months old children in Malawi: a decomposition analysis - Naphiyo, Bridget; Mazalale, Jacob; Chirwa, Gowokani Chijere (Frontiers in Public Health, 2025)
BackgroundGiven the benefits of the Expanded Program on Immunisation (EPI) to Malawians’ health and, consequently, Malawi’s economic development, coverage and equity in immunisation are necessary to track. In the 2019–20 Malawi Multiple Indicator Cluster Survey (MICS), immunisation coverage of basic vaccines among 12-23-month-old children was at 72%. However, disaggregated immunisation coverage in some groups of children was below or above 72%. The disparities compelled the need to investigate the extent of socioeconomic inequalities drivers in child immunisation in Malawi.Study designThis study uses secondary data sets from three of Malawi’s national representative cross-sectional surveys: the Malawi MICS 2013–14, the Malawi MICS 2019–20 and the Malawi Service Provision Assessment (MSPA) 2013–14. The MSPA 2013–14 was used to estimate the shortest distance between a MICS 2019–20 cluster and a facility offering immunisation services.MethodsThe study utilized the concentration index to measure socioeconomic inequality and the Wagstaff decomposition to measure the marginal contributions of socioeconomic factors to inequality.ResultsThe study found no socioeconomic inequality in 2013, but pro-rich inequalities existed in 2019 (0.065 for basic immunisation, 0.09 for age-appropriate immunisation), statistically significant at p < 0.01. Wealth, maternal education and place of residence were significant factors contributing to the pro-rich inequalities in 2019.ConclusionThe results call for interventions that improve affordability and accessibility of vaccines and interventions that educate caregivers of the benefits of child immunisation to ensure equity. The results, therefore, suggest that to improve equality in health outcomes, the Government of Malawi needs to embrace wider policies that do not only address the consumption of healthcare services but also policies that affect socioeconomic determinants of health.